Magnesium Deintercalation From the Spinel‐Type MgMn2‐yFeyO4 (0.4≤y≤2.0) by Acid‐Treatment and Electrochemistry. Issue 49 (20th July 2021) - Medina, Alejandro; Rodríguez, Ana I.; Pérez‐Vicente, Carlos; Alcántara, Ricardo
Abstract: Rechargeable magnesium batteries attract lots of attention because of their high safety and low cost compared to lithium batteries, and it is needed to develop more efficient electrode materials. Although MgMn2 O4 is a promising material for the positive electrode in Mg rechargeable batteries, it usually exhibits poor cyclability. To improve the electrochemical behavior, we have prepared nanoparticles of MgMn2‐y Fey O4 . The XRD results have confirmed that when Mn 3+ (Jahn‐Teller ion) ions are replaced by Fe 3+ (non‐Jahn‐Teller ion), the resulting MgMn2‐y Fey O4 is a cubic phase. The structure and theoretical voltage are theoretically calculated by using the DFT method. The obtained samples have been chemically treated in acid solution for partial demagnesiation, and it is observed that the presence of iron inhibits the deinsertion of Mg through disproportionation and favors the exchange reaction. The electrochemical behavior in non‐aqueous magnesium cells has been explored. Abstract : Nanostructured Mgx Mn2‐y Fey O4 with cubic spinel structures are studied. According to the DFT calculations, the intermediate compositions can be stable, and the voltage could be tailored with the composition. Partial replacement of Mn by Fe could improve the electrochemical cyclability, whereas the Fe would also induce a disorder of the spinel structure, thereby reducing the electrode capacity. The reactions for the acid‐treatment are different for MgMn2 O4 and MgFe2 O4 . The intermediate composition with low iron‐content and acid‐treatment exhibits a good electrochemical behavior.